THE ANALYSIS OF BRAND IMAGE ON PRODUCT PURCHASE DECISIONS AT BLACK CUP COFFEE & ROASTER MANADO - Natanael Owen Rumondor; Joy Elly Tulung; Maria V.J. Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
The formulation of the problem in this study is how does brand image affect purchasing decisions at Black Cup Coffee & Roaster Manado. The aim of this research is to find out how brand image affects purchasing decisions at Black Cup Coffee & Roaster Manado. In this study, the researcher took a descriptive type of research using a qualitative approach because the purpose of this study was to make a systematic, factual, and accurate description, picture, or painting of the facts, characteristics, and relationships between the phenomena being investigated.the researcher concluded that the brand image of a business is sufficient to determine the purchase decision to buy the products offered by business actors, among the most dominant from the informants, namely having their own characteristics and having good product quality, so that it makes customers comfortable and getting used to it. come to Black Cup Coffee and Roaster. The management of Black Cup Coffee & Roaster must pay attention, there are several points that become complaints, namely, coffee quantity is lacking, there is no wifi, only one toilet,insufficient seats and still not comfortable. And it would be nice, all aspects that become complaints must be corrected immediately for the convenience of future customers who come.